2019
DOI: 10.1001/jamainternmed.2019.3893
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Computed Tomography Radiation Doses Used for Lung Cancer Screening Scans

Abstract: ACR) has recognized the importance of minimizing radiation doses used for lung cancer screening (LCS) computed tomography (CT). However, without standard protocols, doses could still be unnecessarily high, reducing screening margin of benefit. OBJECTIVE To characterize LCS CT radiation doses and identify factors explaining variation. DESIGN, SETTING, AND PARTICIPANTSWe prospectively collected LCS examination dose metrics, from 2016 to 2017, at US institutions in the University of California, San Francisco Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Current lung cancer screening protocols recommend repeated screening at either annual or biannual frequency for eligible individuals (10,11). On an individual level this may result in over 25 scans over a lifetime with in practice widely varying cumulative radiation dose (12,13). Consequently, the estimates for induced cancer risk by repeated screening for an entire population vary as well depending on the used CT protocol, CT generation and expertise of institutions to optimize CT protocols (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current lung cancer screening protocols recommend repeated screening at either annual or biannual frequency for eligible individuals (10,11). On an individual level this may result in over 25 scans over a lifetime with in practice widely varying cumulative radiation dose (12,13). Consequently, the estimates for induced cancer risk by repeated screening for an entire population vary as well depending on the used CT protocol, CT generation and expertise of institutions to optimize CT protocols (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…On an individual level this may result in over 25 scans over a lifetime with in practice widely varying cumulative radiation dose (12,13). Consequently, the estimates for induced cancer risk by repeated screening for an entire population vary as well depending on the used CT protocol, CT generation and expertise of institutions to optimize CT protocols (12)(13)(14)(15). The aim of this review is to provide clinicians with an overview of the development of the CT protocol for lung cancer screening, the current protocol recommendations and radiation dose reduction possibilities in lung cancer CT screening.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, emphasis is placed on preferring conservative management of findings with relatively low clinical impact (e.g., control overdiagnosis) by thoracic radiologists and medical physicists. Despite guidelines from the American College of Radiology (ACR) on recommended CT radiation dose levels (13), a cohort study of 12,529 participants at 72 institutions in the US found a wide variation in the distribution of LCS CT doses across facilities (14). According to the authors, 21% of the institutions had median volume computed tomography dose index (CTDI vol ) above ACR benchmarks (>3 mGy).…”
Section: Low-dose Ct Protocolsmentioning
confidence: 99%
“…Studies with large multi-institution or national registry suggest that despite recommendations for reduced dose CT protocols for specific clinical indications and availability of dose monitoring data, adoption of dose-conscious CT protocols remain low [3,4]. Over 65% of participating CT facilities in the USA exceeded the recommended radiation dose level for lung cancer screening with low-dose CT [3].…”
mentioning
confidence: 99%
“…Over 65% of participating CT facilities in the USA exceeded the recommended radiation dose level for lung cancer screening with low-dose CT [3]. Likewise, only 8% of US CT facilities used low-dose CT for kidney stones despite recommendations and evidence within the American College of Radiology Appropriateness Criteria [4]. This pattern hints at a widespread disregard for sufficient diagnostic quality at optimized or reduced radiation dose in favor of convenience, optimization, or medicolegal safety.…”
mentioning
confidence: 99%